CORRELATION STUDY BETWEEN BURDENS AND THE QUALITY OF LIFE IN CAREGIVERS OF DEPENDENT ELDERLY IN PRAWIRODIRJAN VILLAGE - Angelika, Putu Veby; Widagdo, The Maria Meiwati; Manus, Widya Christine; Haripurnomo, Silvester (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Background: Aging is synonymous with decreased body function due to natural factors (aging process) and diseases. The elderly who are unable to do their activities can cause dependence on the caregiver. In carrying out its role, the caregiver has burdens that can affect their life quality. Objective: To measure the correlation between the burden and the quality of life in caregivers of dependent elderly in Prawirodirjan Sub-district, Gondomanan District, Yogyakarta Municipality.Materials and Methods: This study used a cross-sectional method with a total sample of 33 participants. Caregiver burden was measured using the Zarit Burden Interview (ZBI) and Caregiver Reaction Assessment (CRA) questionnaires. Measurements of quality of life were conducted using the WHO QoL BREF questionnaire. Spearman rank correlation analysis was administered to conduct statistical analysis.Results: There were very significant negative correlations between the caregiver’s burden (ZBI) and WHO QoL BREF physical health domain, psychological domain, social relations domain, and environment domain. There were very significant positive correlations between the caregiver’s burden self-esteem caregiver’s domain (CRA) and WHO QoL BREF psychological domain. There was a significant negative correlation between the caregiver's burden of the family support domain (CRA) and WHO QoL BREF physical health domain, psychological domain, social relations domain, and environment domain. There was a significant negative correlation between the caregiver’s burden impacts on the financial domain (CRA) and WHO QoL BREF environment domain. There was a very significant negative correlation between the caregiver’s burden of daily schedule impact domain (CRA) and WHO QoL BREF environment domain as well as there was a very significant negative correlation between the caregiver’s burden of health impact domain (CRA) and WHO QoL BREF physical health domain.Conclusion: There is a significant correlation between burden and the quality of life of dependent elderly caregivers in Prawirodirjan Village, Gondomanan District, Yogyakarta Municipality. The higher the burden of a caregiver, the lower the caregiver's quality of life, and conversely.